A redescription of the Long-tailed Nesokia, Nesokia bunnii, and designation of a neotype (Rodentia: Muridae) - Kryštufek, Boris; Al-Sheikhly, Omar F.; Hutterer, Rainer (Zootaxa, 2017)
Long-tailed Nesokia, Nesokia bunnii, is a large rat restricted to the Mesopotamian marshes in Basra Province in southern Iraq. The species is known from five museum vouchers collected between March 1974 and January 1977. The type and the paratype, deposited in the Natural History Research Centre and Museum, University of Baghdad, Iraq, were destroyed during War on Iraq in 2003. By studying morphological details on three museum specimens in the Senckenberg Institution, Frankfurt a. M., Germany, we show that N. bunnii is unique among the Bandicoot rats (Nesokia and Bandicota) in having (1) rufous dorsal pelage, (2) facial mask of rufous, dark brown, grey and whitish areas, (3) whitish belly which is clearly demarcated along flanks, (4) ventral hairs white to bases, (5) woolly underfur, (6) long front claws, and (7) large tail annulation. Similar to N. indica, but in contrast to Bandicota, N. bunnii displays short incisive foramina, posterior margin of hard palate which terminates at the level of the third molar, and robust, hypsodont and laminate molars which lack posterior cingula. To objectively define the taxon we designate a neotype, which was collected at Saraifa, 30 km north of Qurna, Iraq. Our study highlights the importance of museum collections in documenting biodiversity and the indifference of decision makers and international institutions regarding their safe future.